2021
DOI: 10.1055/a-1589-6301
|View full text |Cite
|
Sign up to set email alerts
|

Baseline Working Memory Predicted Response to Low-Dose Ketamine Infusion in Patients with Treatment-Resistant Depression

Abstract: Introduction Pretreatment neurocognitive function may predict the treatment response to low-dose ketamine infusion in patients with treatment-resistant depression (TRD). However, the association between working memory function at baseline and the antidepressant efficacy of ketamine infusion remains unclear. Methods A total of 71 patients with TRD were randomized to one of three treatment groups: 0.5 mg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Moreover, higher body mass index was correlated with a greater reduction in the 17-item Hamilton Depression Rating Scale (HAM-D-17) total score at 1 d and 230 min after ketamine infusion in patients with MDD and BD [10]. Other studies have reported the association of following factors with better response to ketamine treatment: lower number of treatment failures and lower baseline severity of illness [11], younger age and no history of neuromodulation treatment [12], lower baseline intelligence quotient [13], lower pretreatment working memory function [14], lower adiponectin [15], higher brain-derived neurotrophic factor (BDNF) after ketamine administration [16], single nucleotide polymorphism (SNP) in the Val/Val BDNF allele at rs6265 [17], and smaller left hippocampal volume [18]. However, these studies had several limitations, such as the study design heterogeneity (e. g., a combination of open-label and randomized placebo-controlled trials, including both MDD and BD).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, higher body mass index was correlated with a greater reduction in the 17-item Hamilton Depression Rating Scale (HAM-D-17) total score at 1 d and 230 min after ketamine infusion in patients with MDD and BD [10]. Other studies have reported the association of following factors with better response to ketamine treatment: lower number of treatment failures and lower baseline severity of illness [11], younger age and no history of neuromodulation treatment [12], lower baseline intelligence quotient [13], lower pretreatment working memory function [14], lower adiponectin [15], higher brain-derived neurotrophic factor (BDNF) after ketamine administration [16], single nucleotide polymorphism (SNP) in the Val/Val BDNF allele at rs6265 [17], and smaller left hippocampal volume [18]. However, these studies had several limitations, such as the study design heterogeneity (e. g., a combination of open-label and randomized placebo-controlled trials, including both MDD and BD).…”
Section: Resultsmentioning
confidence: 99%
“…Working memory and go/no-go tasks were performed prior to infusion (Chen et al, 2022;Zimmermann, 1997). In the go/no-go task, participants were asked to respond as quickly as possible after the × symbol appeared.…”
Section: Cognitive Function Assessment At Baselinementioning
confidence: 99%
“…They also identified an inverse correlation between cognitive function and NFL concentration among patients with major depressive disorder; a higher NFL concentration was associated with poorer cognitive function ( Bavato et al, 2021 ). Our previous study suggested an association between baseline cognitive function and response to treatment with ketamine infusion ( Chen et al, 2022a ). This inspired us to further elucidate the role of baseline NFL concentrations in the antidepressant effects of low-dose ketamine.…”
Section: Introductionmentioning
confidence: 99%